Strengthening Management of Religious Moderation Education Hidden Curriculum In Pancasila Village (Case Study in Gaprang Village, Blitar District, East Java Province, Indonesia) - Tri Prasetiyo Utomo; Imam Saerozi; Juhan Budiwan (International Journal of Science and Applied Science: Conference Series, 2024)
Abstract: Religious moderation is a perspective in building harmony in a multicultural Indonesian society. Cultural diversity in Indonesia is God's destiny that contains a potential. The potential to get to know each other, work together, and complement each other in a framework of pluralistic harmony. However, this multiculturalism can be a threat if not managed properly. Therefore, it is necessary to provide education to the community about the values of religious moderation through a hidden curriculum. This study uses a qualitative phenomenological naturalistic approach. The goal is to understand and interpret in-depth behavioral interactions about the management of religious moderation education based on the hidden curriculum in the Pancasila village of Gaprang, Blitar. The results of the study show that the management of strengthening religious moderation education is hidden curriculum through; 1) implicit messages in the village cleaning ritual (baritan, cultural procession, and nyadran). 2) unspoken messages of taking jamasan water from various sources in Gaprang village, joint prayers, and UMKM. 3) Building cultural ties and community organizational structures is marked by the construction of the masgapur gate, an acronym for mosque, church, and temple.